Toothbrush Contamination: A Review of the Literature - Michelle R. Frazelle; Cindy L. Munro (Hindawi Limited, 2012)
Toothbrushes are commonly used in hospital settings and may harbor potentially harmful microorganisms. A peer-reviewed literature review was conducted to evaluate the cumulative state of knowledge related to toothbrush contamination and its possible role in disease transmission. A systematic review was conducted on adult human subjects through three distinct searches. The review resulted in seven experimental and three descriptive studies which identified multiple concepts related to toothbrush contamination to include contamination, methods for decontamination, storage, design, and environmental factors. The selected studies found that toothbrushes of healthy and oral diseased adults become contaminated with pathogenic bacteria from the dental plaque, design, environment, or a combination of factors. There are no studies that specifically examine toothbrush contamination and the role of environmental factors, toothbrush contamination, and vulnerable populations in the hospital setting (e.g., critically ill adults) and toothbrush use in nursing clinical practice.